An Analysis of Students’ Experience in Using English Learning Application “myON” in Helping Students’ English Learning Process - Fasya Putri Radhiyya; Nazwa Aulia; Syifa Shabrina; Hairunnisa Aulia Putri; Bambang Nur Alamsyah Lubis (SCHOULID: Indonesian Journal of School Counseling, 2023)
Generally, teaching and learning activities mostly rely on books, instructional materials provided by teachers, and written or verbal exercises. These learning approaches are monotonous. Given the progress of technology and the internet, it is necessary for educators to utilize technology-driven online learning platforms, such as myON applications. This will be achieved by employing qualitative research methodologies to investigate the students' experiences and perspectives on the utilization of the “myON” application for English learning. A Google Form questionnaire is utilized and distributed using the messaging platform Whatsapp. Data analysis include the utilization of narrative methodologies to effectively and accurately summarize and depict the outcomes of questionnaires, which are derived from the experiences of students. The study centered on students in the IX-B Grade of Al-Fityan High School in Medan Selayang, Sumatera Utara. Its objective was to examine the level of student engagement and enthusiasm in utilizing online learning tools, while also seeking to enhance accuracy through feedback obtained from questionnaires. The app received positive feedback from students in class IX B, who expressed satisfaction with its simple design and its positive influence on their English proficiency. While the majority experienced significant improvements in their writing, reading, listening, and grammatical skills, a few individuals indicated dissatisfaction, citing intricate explanations, high costs, and a perception of monotonous. Hence, it is imperative for the "myON" application to underscore the significance of this tool in the process of English language acquisition by showcasing improved functionalities and enhanced communication capabilities that correspond with user preferences.